Sosialisasi Sanitasi Dan Higienitas Sarapan Untuk Anak Sekolah Selama Masa Pandemi Di Desa Kulati - Ode Yahyu Herliany Yusuf (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The purpose of doing this community service (PKM) is so that parents understand and know the requirements of preparing breakfast for children before starting learning activities while at home, by introducing the importance of sanitation and hygiene in dishes. The activity was carried out in Kulati Village, Tomia District, Wakatobi Regency, and went according to plan. The expectation from the activity is that parents will focus more on their children's breakfast needs in accordance with the sanitation and hygiene of the kitchen of each house.